2016
DOI: 10.1160/th15-11-0871
|View full text |Cite
|
Sign up to set email alerts
|

Antithrombin Dublin (p.Val30Glu): a relatively common variant with moderate thrombosis risk of causing transient antithrombin deficiency

Abstract: The key haemostatic role of antithrombin and the risk of thrombosis associated with its deficiency support that the low incidence of antithrombin deficiency among patients with thrombosis might be explained by underestimation of this disorder. It was our aim to identify mutations in SERPINC1 causing transient antithrombin deficiency. SERPINC1 was sequenced in 214 cases with a positive test for antithrombin deficiency, including 67 with no deficiency in the sample delivered to our laboratory. The p.Val30Glu mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 42 publications
1
24
0
Order By: Relevance
“…Afterwards, since mutations that are not usually detected by current functional assays and that are responsible for transient AT deficiencies are usually located in exons 2 and 7, these exons were sequenced in the whole cohort of 89 patients. One mutation was found: Patient 3 was a 51 year‐old‐woman with a known MPN that during follow‐up developed a portal and splenic vein thrombosis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Afterwards, since mutations that are not usually detected by current functional assays and that are responsible for transient AT deficiencies are usually located in exons 2 and 7, these exons were sequenced in the whole cohort of 89 patients. One mutation was found: Patient 3 was a 51 year‐old‐woman with a known MPN that during follow‐up developed a portal and splenic vein thrombosis.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it has been reported that the pathogenic effect of some SERPINC1 mutations might be exacerbated by environmental factors, leading to transient AT deficiency that would only be detected by functional methods. This would be the case of SERPINC1 mutation p.Val30Glu . Patients with this mutation would have normal levels and function of AT in baseline conditions but with a higher conformational susceptibility to stress, which would lead to deficiency of AT .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Congenital thrombophilia is caused by a wide variety of genetic abnormalities (being antithrombin deficiency the strongest one) and results in permanent risk for recurrent thrombosis1. Moreover, the presence of an acquired factor at specific time-points may further disturb the already unbalanced hemostatic system or trigger the pathological effects of certain mutations that can lead to thrombotic events2. Unfortunately, to date only a small number of genetic and acquired factors involved in thrombosis have been identified.…”
mentioning
confidence: 99%
“…Most of the associated conditions cause multiple abnormalities of the coagulation cascade and alter levels of both pro and anti-coagulants [9–11]. Table 3 outlines some of the common causes of acquired ATIII deficiency.…”
Section: Introductionmentioning
confidence: 99%